Camouflaging in Autism: Examining Sex‐Based and Compensatory Models in Social Cognition and Communication. Issue 1 (21st November 2020) - Corbett, Blythe A.; Schwartzman, Jessica M.; Libsack, Erin J.; Muscatello, Rachael A.; Lerner, Matthew D.; Simmons, Grace L.; White, Susan W.
Abstract : Abstract: Camouflaging refers to behavioral adaptations that individuals with autism spectrum disorder (ASD), especially females, use to mask symptoms during social situations. Compensation is a component of camouflaging in which an individual's observed behavior is considerably better than actual ability. The study explored diagnostic, sex‐based, and compensatory differences using the Contextual Assessment of Social Skills (CASS). The sample included 161 youth 10:0‐to‐16:11 years (115 males, 46 females). T‐tests were performed based on sex (female, male) or High (good ADOS + poor Theory of Mind (TOM)) compared to Low (poor ADOS + poor TOM) Compensation groups. Comparisons were examined for Social Affect (SA), Restricted Repetitive Behavior, (RRB), IQ, social behavior (Positive Affect, Overall Involvement) and communication (Vocal Expression, Gestures). Females exhibited fewer RRB t (158) = 3.05, P = 0.003, d = 0.54. For the CASS, females evidenced more Vocal Expressiveness t (157) = −2.03, P = 0.05, d = 0.35, which corroborates sex‐based differences in the literature. Compensation group differences indicated the High compared to Low group showed stronger Social and Communication behaviors on the CASS for Vocal Expression t (72) = 2.56, P = 0.01, d = 0.62, and overall rapport t (72) = 2.36, P = 0.02, d = 0.56. Several differences were observed when the groups were stratified based on level of compensation, with the High compensation participants showing stronger social engagement and communication behaviors. Findings may inform efforts to understand camouflaging, compensation, and clinical practices for male and female adolescents with ASD. A more nuanced consideration of camouflaging alongside compensation models reveals subtle differences in cognition, behavior, and affect that may reflect underlying profiles of challenge and strength in youth with ASD. Lay Summary: Camouflaging refers to ways individuals with autism spectrum disorder (ASD), especially females, mask symptoms. Compensation occurs when a person's observed behavior appears more typical than what would be expected based on underlying ability and symptoms. The study explored camouflaging and compensation differences in 161 youth with ASD. Findings suggest sex‐based differences with females showing better vocal expression. However, several compensation differences were observed with the High compensators showing stronger social communication and rapport. A more nuanced consideration of camouflaging using compensation models reveal subtle differences in underlying challenge and strength.